The Importance of Implementation of Hand Hygiene Practice in Reducing Healthcare-associated Infections: A Systematic Review - Andriani, Y; Nadjib, M (KnE Life Sciences, 2018)
Healthcare-associated Infections (HAIs) become the priority attentions of health authorities worldwide because it became the most frequent adverse event of infections in the health care system. Hand hygiene is the effective way in preventing HAIs since healthcare personnel’s hands frequently serve as vectors in transmission of organism from personnel’s hands to patient’s, and for that reason, hand hygiene become important to patient safety. Although it is seen as the most important way to reduce HAIs’ rate, hand hygiene compliance among healthcare professionals continues to be low, and most efforts to improve it have failed. This study aims to assess the hand-hygiene practices in health workers in order to reduce HAIs. The study is a systemic review with PRISMA method, articles were downloaded from online databases such as ProQuest and SAGE using keywords hand hygiene, hand washing, and Healthcare-associated Infections. The period of the articles that had been review is 10 years backwards. After the title was selected, the next step was to read the abstract and full article. Authors determined 11 articles in qualitative synthesis study to be reviewed. As a result, there were 11 journal articles, 10 of which were on observational studies and 1 was an experimental interventional study. Four of the articles were based on systematic review analysis and the rest of the articles were based on statistics analysis. Half of the studies in this systematic review were done in the American region, two studies in European regions and three studies in Asian regions that included Thailand, Saudi Arabia, Shanghai, and China. From all of the articles, only five showed a positive association between implementation of hand hygiene and HAIs. The positive articles gave information that the practice of hand hygiene significantly decreases HAIs’ rate. This systematic review proved that hand hygiene is clearly effective to reduce HAIs’ rate. Improvement of hand hygiene practice resulted in reduction of both gastrointestinal illness and respiratory illness. In practice, more women than men wash their hands and between health workers, nurses achieve higher compliance than physicians. Even when hand hygiene is proven to be the best way to reduce HAIs, the compliance of hand washing still lacks and needs more monitoring and strategies to improve. Keywords: hand hygiene, hand washing, Healthcare-associated Infections